Spatiotemporal role of transforming growth factor beta 2 in developing and mature mouse hindbrain serotonergic neurons - Chleilat, Enaam; Mallmann, Robert Theodor; Spanagel, Rainer; Klugbauer, Norbert; Krieglstein, Kerstin; Roussa, Eleni (Frontiers in cellular neuroscience, 2019)
Transforming growth factor betas are integral molecular components of the signalling cascades defining development and survival of several neuronal groups. Among TGF-β ligands, TGF-β2 has been considered as relatively more important during development. We have generated a conditional knockout mouse of the Tgf-β2 gene with knock-in of an EGFP reporter and subsequently a mouse line with cell-type specific deletion of TGF-β2 ligand from Krox20 expressing cells (i.e., in cells from rhombomeres r3 and r5). We performed a phenotypic analysis of the hindbrain serotonergic system during development and in adulthood, determined the neurochemical profile in hindbrain and forebrain, and assessed behavioural performance of wild type and mutant mice. Mutant mice revealed significantly decreased number of caudal 5-HT neurons at embryonic day (E) 14, and impaired development of caudal dorsal raphe, median raphe, raphe magnus, and raphe obscurus neurons at E18, a phenotype that was largely restored and even overshot in dorsal raphe of mutant adult mice. Serotonin levels were decreased in hindbrain but significantly increased in cortex of adult mutant mice, though without any behavioural consequences. These results highlight differential and temporal dependency of developing and adult neurons on TGF-β2. The results also indicate TGF-β2 being directly or indirectly potent to modulate neurotransmitter synthesis and metabolism. The novel floxed TGF-β2 mouse model is a suitable tool for analysing the in vivo functions of TGF-β2 during development and in adulthood in many organs.
Gesehen am 21.02.2020